Energy and Economic Myths : Institutional and Analytical Economic Essays. - Georgescu-Roegen, Nicholas (Elsevier Science, 2014)
Energy and Economic Myths: Institutional and Analytical Economic Essays is a collection of materials that deal with various issues and concerns in economics. The title aims to clarify the misconception in economics. The first part of the text deals with the issues in natural resources and the economics of production. Next, the selection tackles the problems in institutional economics. Part III covers the epistemological and methodological concerns in economics. The title also talks about economic theories. The book will be of great interest to economists and readers who want to enhance their u.